UJI EFEK KOMBINASI EKSTRAK DAUN ALPUKAT (Persea americana Mill.) DAN DAUN SRIKAYA (Annona squamosa L.) SEBAGAI ANTIOBESITAS PADA TIKUS JANTAN - Wati, Aulia; Asmaliani, Ira; Herman, Hendra; Fira, Alfiah (As-Syifaa Jurnal Farmasi, 2023)
Obesity is a condition where there is a buildup of excess body fat so that a person's weight is far above normal.  This study aims to determine the effectiveness  of the combination of avocado leaf extract (Persea americana Mill. ) and srikaya leaves (Annona squamosa L.) as antiobesity in male rats. This study used 18 mice. Rats were given high-fat carbohydrate feed as much as 25 grams a day for 28 days to get obese conditions, followed by oral trial preparation therapy for 14 days with dose variations, namely group I (negative control), group II (positive control), group III avocado leaf extract 60 mg / kg BB, group IV srikaya leaf extract 125 mg / kg BB,  group V extract combination small dose avocado leaf extract 60 mg/kgBB and srikaya leaf 125 mg/kgBB, and group VI extract combination large dose avocado leaf extract 120 mg/kgBB and srikaya leaf extract 250 mg/kgBB. Measurement  of the  Lee index of  test animals was carried out before induction, after induction and after therapy then continued with surgery to determine the weight of perianal, perirenal, and peritonial fat. The results showed that a combination extract of small doses of avocado leaves 60 mg/kgBB and srikaya leaves 125 mg/kgBB had the most effective effect compared to other treatment groups